Atomic worlds: Current state and future of atom probe tomography in geoscience. (15th April 2018) - Saxey, D.W.; Moser, D.E.; Piazolo, S.; Reddy, S.M.; Valley, J.W.
Abstract: Atom Probe Tomography (APT) is rapidly finding new applications within the geosciences. Historically connected with materials science and semiconductor device applications, recent years have seen APT established as a useful tool for nanoscale geochemistry, offering unique capabilities when compared with conventional geoanalytical techniques. The ability to characterize 3D nanoscale chemistry with isotopic sensitivity has uncovered intricate details of complex trace element distributions within a variety of minerals. Already these advances are having an impact on long-standing questions within geochronology, planetary science and other fields. Future developments are likely to bring significant expansion in this research space.